Prescription Writing Errors of Midwifery Students in Common Gynecological problems - Serveh Parang; Nahid Golmakani; Gebraeil Movaffaq; Hossein Jafari Sani (Mashhad University of Medical Sciences, 2014)
Background and aim: Giving improper prescriptions is common among medical practitioners, mostly graduates, in most communities even developed countries. So far, to our knowledge, no study has been conducted on prescription writing of graduate midwifery students. Therefore, this study aimed to detect prescription writing errors of midwifery students in common gynecological problems. Methods: In this descriptive cross-sectional study, 56 bachelor midwifery students, who had passed the theoretical and clinical courses of gynecology, were evaluated by Objective Structured Clinical Examination (OSCE). A demographic questionnaire and a standard checklist for writing the prescriptions and medications were used for data collection. SPSS Version 16 was used to carry out descriptive statistics. Findings: Most of the students were single, with the mean age of 23.0±1.7 years. Most errors were related to not recording the patients' age and sex, diagnosis, chief complaint, and the prescriber's name (observed in less than 10% of the prescriptions). The complete dosage schedule and drug name were stated only in 1.8±4.8 and 14±18.6 of prescriptions, respectively. In more than 93% of the cases, route of use and treatment duration were not recorded. Conclusion: According to the results, the number of prescription errors of midwifery students was high. Therefore, it is recommended to run educational courses on prescription writing skills (e.g. writing prescriptions based on World Health Organization (WHO) guidelines) for the midwifery students.